Comparison of the efficacy and safety of 4 and 2 mg/day brexpiprazole for acute schizophrenia: a meta-analysis of double-blind, randomized placebo-controlled trials - Kishi T (Dove Medical Press, 2018)
Taro Kishi,1 Kazuto Oya,1 Yuki Matsui,1,2 Ikuo Nomura,1 Kenji Sakuma,1 Makoto Okuya,1 Yuki Matsuda,3 ,Kiyoshi Fujita,4 Toshihiko Funahashi,2 Reiji Yoshimura,5 Nakao Iwata1 1Department of Psychiatry, Fujita Health University School of Medicine, Toyoake, Aichi 470-1192, Japan; 2Department of Psychiatry, Jindai Hospital, Toyota, Aichi 470-0361, Japan; 3Department of Psychiatry, Jikei University School of Medicine, Minato-ku, Tokyo105-8461, Japan; 4Department of Psychiatry, Okehazama hospital, Toyoake, Aichi 470-1168, Japan; 5Department of Psychiatry, University of Occupational and Environmental Health, Yahatanishi-ku, Kitakyushu, Fukuoka 807-8555, Japan Purpose: The purpose of this study was to compare the efficacy and safety of brexpiprazole 4 mg/day (B4) and 2 mg/day (B2) for treating acute schizophrenia. Patients and methods: We performed three categorical meta-analyses (B4 vs placebo, B2 vs placebo, and B4 vs B2) of double-blind, randomized placebo-controlled trials (DBRCTs) that reported improvements in the Positive and Negative Syndrome Scale (PANSS) scores, response rate, Clinical Global Impression–Improvement and Severity (CGI-I and CGI-S) scores, discontinuation rate, and incidence of individual adverse events. Results: We identified three DBRCTs with 1,444 patients. Both B4 and B2 were superior to placebo for PANSS total score (B4: standardized mean difference [SMD] =-0.30, 95% CI =-0.43, -0.17; B2: SMD =-0.30, 95% CI =-0.46, -0.13), PANSS negative score, response rate, CGI-S score, and CGI-I score. B2, but not B4, was superior to placebo for the PANSS positive score. However, there was considerable heterogeneity in the meta-analysis for B4’s PANSS positive score, which disappeared after excluding a 2018 Japanese study from the meta-analysis that included more patients on a high-dose antipsychotic prior to their participation. A meta-analysis that excluded the data from the abovementioned patients showed B4 to be superior to the placebo in terms of the PANSS positive score (SMD =-0.22, 95% CI =-0.40, -0.03). B2, but not B4, was associated with a lower incidence of all-cause discontinuation compared with placebo. Both B4 and B2 were superior to placebo for discontinuation due to adverse events and schizophrenia, but both were associated with a higher incidence of weight gain compared with placebo. B4 was also associated with a higher risk of extrapyramidal symptoms than B2. Conclusion: Both B4 and B2 benefitted patients with schizophrenia, particularly those who were not previously on high-dose antipsychotics. Both the regimens were well-tolerated, but carried a risk of weight gain and extrapyramidal symptoms, although the latter risk was higher for B4 than B2. Keywords: schizophrenia, brexpiprazole 2 mg/day, brexpiprazole 4 mg/day, Positive and Negative Syndrome Scale score, response rate, safety outcomes, systematic review, meta-analysis